Prescribing trends of HMG Co-A reductase inhibitors in outdoor patients at tertiary care teaching hospital of central India: a retrospective observational study - T. Bhagwate, Sudharam; S. Harwani, Renuka; S. Jeswani, Dheeraj; N. Yalgundee, Sagar; Warbhe, Rupesh A. (International Journal of Basic & Clinical Pharmacology, 2018)
Background: To analyze the prescribing patterns of statins a hypolipidemic agents by using HMIS database in outdoor patients at tertiary care teaching hospital of central India. Methods: In this retrospective study Using HMIS database, 1000 prescriptions were analyzed for statin use for various WHO prescription indicators using ATC code of statins, the ratio of prescribed daily dose (PDD) and defined daily dose (DDD) was calculated. Results: Atorvastatin was the only statin which was prescribed as monotherapy (61.1%), whereas as combination with aspirin (38.9%). While analyzing the prescriptions, it was found that patients having abnormal lipid profiles (51.8%) and normal lipid profiles (48.2%) were prescribed atorvastatin. Hypertension with diabetes (37%) was the most common disease followed by hypertension (21.2%) and diabetes mellitus (21%) for which atorvastatin was prescribed. The average number of drugs per prescription were 3.8±1.65. Conclusions: This study depicts the use of atorvastatin in various disease conditions, both as primary and secondary preventive measures. There was no polypharmacy. Such studies should be done to educate the physicians on good prescribing practices and to rationalize use of hypolipidemic drugs.